Biblioteca universitária híbrida no contexto da Web 2.0: o caso da Biblioteca da Escola de Enfermagem da UFRGS - Silva Filho, Rubens da Costa (2015)
In the current technological context, we can see the relevance of university libraries seek new ways to keep and expand its reach and interaction with its users. A greater library visibility allows its users to know what the library can offer them and to increase their access to scientific knowledge. It is up to information units get new features that captivate their users and at the same time allow the library to expand its reach to potential users. Thus, the main aim of this research is to investigate best practices to promote and publicize the Library of UFRGS’s School of Nursing (BIBENF) using Web 2.0 tools. This is a case study with an exploratory proposal and using both quantitative and qualitative approaches. We used the following electronic instruments to collect data: questionnaires, analysis of activities in the library profile on Facebook, and Google Analytics reports. The sample is composed by the academic community of UFRGS School of Nursing, graduates, workers from nursing area in the Hospital de Clínicas de Porto Alegre, linked individuals to the School of Public Health - RS, registered professionals in the Conselho Regional de Enfermagem e Associação Nacional de Enfermagem - RS, followers of BIBENF profile on Facebook and users who accessed the library website. The data obtained show Facebook as the most used Web 2.0 tool. The WhatsApp is the most suggested tool for use by BIBENF. The data analysis of website points to a not limited geographical coverage, since only 30% of the users are from Porto Alegre, where BIBENF is located. A manual of best practices in the use of Web 2.0 tools for the promotion and dissemination of university libraries was constructed as a professional master’s outcome. The results showed the importance of also identify the needs of potential users of the services offered by Web 2.0 tools. We conclude that the intensive use of such tools, as a means of promotion and dissemination, could meet in a more effective way to the informational needs of its real and potential users. The usage of these tools also improves the customer loyalty in the use of services and products developed by the library.